Multi-objective control allocation - Jamil, Ramey (Cranfield University, 2012)
Performance and redundancy requirements imposed on state-of-the-art unmmaned combat aerial vehicles often lead to over-actuated systems with a mix of conventional and novel moment generators. Consequently, control allocation schemes have become a crucial part of the flight control architecture and their design is now a growing problem. This thesis presents a four control allocation scheme designed to meet multiple objectives and resolve objective conflicts by finding the ‘Pareto’ optimal solution, namely; Weighted Control Allocation, Minimax Control Allocation, Canonical Control Allocation and Classical. This is defined as a solution to the multi-objective optimisation problem which is non-dominated for all objectives. The scheme is applied to a six degrees of freedom nonlinear simulation of an aircraft equipped with conventional control surfaces as well as fluidic thrust vectoring and circulation control. The results indicate a perfect allocation of the total control demand onto the actuator suite.